2018
DOI: 10.1177/1367493518807325
|View full text |Cite
|
Sign up to set email alerts
|

User testing digital, multimedia information to inform children, adolescents and their parents about healthcare trials

Abstract: Digital, multimedia information resources (MMIs) containing text, video, animation and pictures are a promising alternative to written participant information materials designed to inform children, adolescents and parents about healthcare trials, but little research has tested whether they are fit for purpose. This study employed a consecutive groups design and user testing questionnaire to assess whether participants were able to find and understand key information in multimedia resources. Two rounds of testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Participant information, participant knowledge and social influences were found to act both as barriers and facilitators, and this perhaps presents a problem. First, researchers are unlikely to be able to control for social influences; second, information to inform research participation is mostly universal in provision and highly regulated [48], and yet amongst patients there can be strong, individual preferences for the quantity and complexity of information [49][50][51][52]. The opposing forces of universalism and individual preferences can be hard to reconcile, although digital provision does increase the potential for information to be tailored or personalised, whether by the originator or recipient.…”
Section: Meaning Of the Study: Possible Explanations And Implicationsmentioning
confidence: 99%
“…Participant information, participant knowledge and social influences were found to act both as barriers and facilitators, and this perhaps presents a problem. First, researchers are unlikely to be able to control for social influences; second, information to inform research participation is mostly universal in provision and highly regulated [48], and yet amongst patients there can be strong, individual preferences for the quantity and complexity of information [49][50][51][52]. The opposing forces of universalism and individual preferences can be hard to reconcile, although digital provision does increase the potential for information to be tailored or personalised, whether by the originator or recipient.…”
Section: Meaning Of the Study: Possible Explanations And Implicationsmentioning
confidence: 99%
“…The TRECA study websites drew on extensive underpinning qualitative research ( Martin-Kerry et al, 2019 ) and user testing ( Sheridan et al, 2019 ), and were informed by principles of Plain English and information design ( Knapp et al, 2011 ), as well as age-appropriateness and readability formulae ( Readabilityformulas.com ). The TRECA Patient and Public Involvement Group commented on the content and design of the websites throughout their development ( Sheridan et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…A higher DMQ score indicates better quality of decision-making. The DMQ comprised items evaluating aspects of trial participation decision-making indicated as important in the underpinning empirical work ( Martin-Kerry et al, 2017 , 2019 ; Sheridan et al, 2019 , 2020b ), including items on: information content; the experience of participation; uncertainty in trials; participation advantages and disadvantages; the process of decision-making; and decisional confidence. The nine scale items were followed by three free-text questions that asked respondents: to suggest any additional information they would have wanted; to identify aspects that were explained well; and for any other comments.…”
Section: Methodsmentioning
confidence: 99%
“…In Phase 1, prototype MMIs containing text, animations, video and pictures were developed with input from study participants including children, young people, families and health-care professionals, to ensure they met people's needs and preferences . The MMIs were then user tested to ensure that they were understandable and intuitive to use (Sheridan et al, 2019). Examples from the TRECA MMIs are available at: https://morph.co.uk/case-study/treca/.…”
Section: The Treca Studymentioning
confidence: 99%